L’œuvre de miséricorde du Roi : la statue de Louis XIV pour l’Hôtel de Ville de Paris par Antoine Coysevox, 1687-1689 - Alexandra Woolley (Les Cahiers de Framespa)
This paper offers an iconographical analysis of Antoine Coysvox’s bronze statue of Louis XIV. The King authorized this new effigy during the 1687 Parisian festivities that commemorated his miraculous recovery from illness. Coysevox’s statue, revealed to the public in 1689, not only became the symbol of an official reconciliation between Paris and Versailles, but also became an occasion to promote the image of the Very Christian King. The bas-reliefs that adorn the statue’s pedestal state in allegorical language Louis XIV’s Catholic virtues. The first one shows Piety feeding the poor, commemorating the bread that was given out to the Parisians during the famine of 1662. This royal charitable action of « feeding the hungry », a work of mercy, is associated with the iconography of the second bas-relief which represents Religion striking down Heresy, celebrating the Revocation of the Edict of Nantes, decided in 1685. These allegorical compositions thus appear as a proselytizing advocacy, attesting that the King not only fed his subjects’bodies, but he also nourished their souls, sealing Louis XIV’s political and religious authority on Paris.